2013
DOI: 10.1371/journal.pone.0064065
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Occupational Stress Is Associated with Regional Reductions in Brain Tissue Volumes

Abstract: There are increasing reports of cognitive and psychological declines related to occupational stress in subjects without psychiatric premorbidity or major life trauma. The underlying neurobiology is unknown, and many question the notion that the described disabilities represent a medical condition. Using PET we recently found that persons suffering from chronic occupational stress had limbic reductions in the 5-HT1A receptor binding potential. Here we examine whether chronic work-related stress is also associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
95
2
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(112 citation statements)
references
References 89 publications
9
95
2
4
Order By: Relevance
“…These findings are in line with our previous observation based on PET measurements of resting state connectivity [22], although the methodology and participant sample were different. They are also in accordance with the reduction of gray matter volume in the dlPFC and ACC and the cortical thinning of the mPFC observed in subjects suffering from occupational stress [21],[23]. Taken together, these data support the postulation that stress-processing limbic networks are affected in subjects suffering from occupational burnout.…”
Section: Discussionsupporting
confidence: 88%
“…These findings are in line with our previous observation based on PET measurements of resting state connectivity [22], although the methodology and participant sample were different. They are also in accordance with the reduction of gray matter volume in the dlPFC and ACC and the cortical thinning of the mPFC observed in subjects suffering from occupational stress [21],[23]. Taken together, these data support the postulation that stress-processing limbic networks are affected in subjects suffering from occupational burnout.…”
Section: Discussionsupporting
confidence: 88%
“…As it has been repeatedly observed that chronic stress leads to a reduction in hippocampal volume, the authors concluded that enduring negative stressful life events may have differential short-and long term effects on the hippocampus. Recent magnetic resonance imaging studies found no differences in the structural volume of the hippocampus between patients suffering from chronic occupational stress for at least one year and healthy controls (Blix et al, 2013;Savic, 2015). This outcome might also be interpreted with regard to delayed effects of stress on the hippocampus, indicating that the duration of stress exposure was not long enough for visible morphological changes.…”
Section: Hippocampal Volume and Burnoutmentioning
confidence: 91%
“…This hypothesis is supported by imaging studies that evidenced structural changes in the brain of individuals suffering from various types of stress-related disorders, such as those linked to severe traumas, major negative life events or chronic psychosocial strain. In particular, Blix and colleagues observed atrophy of the basal ganglia and significantly reduced gray matter in certain areas of the PFC in subjects afflicted with long-term occupational stress [5]. In general, the consequences of these alterations in a brain region can expand to other functionally connected areas, and potentially cause those cognitive, emotional and behavioral dysfunctions that are commonly associated with chronic stress, and that may increase vulnerability to psychiatric disorders.…”
Section: What Is the Actual Impact Of Chronic Stress On Health?mentioning
confidence: 99%